Laser-Induced Graphite Plasma Kinetic Spectroscopy under Different Ambient Pressures*Supported by the FRGS under Grant No R.J130000.7809.4F519. (April 2015) - Chaudhary, K.; Rosalan, S.; Aziz, M. S.; Bohadoran, M.; Ali, J; Yupapin, P. P.; Bidin, N.; Saktioto,
Abstract : The laser induced plasma dynamics of graphite material are investigated by optical emission spectroscopy. Ablation and excitation of the graphite material is performed by using an 1064nm Nd:YAG laser in different ambient pressures. Characteristics of graphite spectra as line intensity variations and signal-to-noise ratio are presented with a main focus on the influence of the ambient pressure on the interaction of laser-induced graphite plasma with an ambient environment. Atomic emission lines are utilized to investigate the dynamical behavior of plasma, such as the excitation temperature and electron density, to describe emission differences under different ambient conditions. The excitation temperature and plasma electron density are the primary factors which contribute to the differences among the atomic carbon emission at different ambient pressures. Reactions between the plasma species and ambient gas, and the total molecular number are the main factors influencing molecular carbon emission. The influence of laser energy on the plasma interaction with environment is also investigated to demonstrate the dynamical behavior of carbon species so that it can be utilized to optimize plasma fluctuations.